Neuroprotective effects associated with immune modulation by selected lactic acid bacteria in a Parkinson's disease model - Pérez Visñuk, Daiana Emilce (2020)
Objectives: Parkinson's disease (PD) is a neurodegenerative process that affects the motor function and involves an inflammatory response and B vitamin deficiencies. The aim of this study was to evaluate the effect of B-group vitamin-producing and immunomodulatory lactic acid bacteria (LAB) in a murine model of PD. Methods: The effect of Lactobacillus plantarum CRL 2130 (a riboflavin producer), Streptococcus thermophilus CRL 807 (an immunomodulatory strain), and Streptococcus thermophilus CRL 808 (a folate producer) were evaluated individually and as a mixture in mice injected with 1-methyl-4-fenil-1,2,3,6-tetrahidropiridina. Motor capacity, tyrosine hydrolase in the brain, and cytokine concentrations in serum and brain tissues were evaluated in 1-methyl-4-fenil-1,2,3,6-tetrahidropiridina-treated mice after bacterial supplementation. Results: The mice receiving the selected LAB showed significantly improved motor skills compared with those that did not receive bacterial supplementation. When given the mixture of all 3 strains together, the animals had higher brain tyrosine hydrolase-positive cell counts, decreased inflammatory cytokines interleukin 6 and tumor necrosis factor alpha in serum, and increased antiinflammatory cytokine interleukin 10 in serum and brain tissues compared with animals that did not receive LAB supplementation. Conclusions: The results showed the potential of a selected LAB mixture to improve motor behavior and neuroinflammation in PD. This probiotic mixture could be used as an adjunct treatment in the control of PD.